The Effect of Profitability, Growth Opportunity and Capital Structure on Firm Value with Good Corporate Governance as Moderation - Rahmawati, Meyssy Trisa; Rahmawati, Ika Yustina; Tubastuvi, Naelati; Alfalisyado, Alfalisyado (PT FORMOSA CENDEKIA GLOBAL, 2024)
The business world is growing. The birth of small and large companies has become a common phenomenon. This study was conducted with the aim of testing income, growth opportunities and capital structures on the value of haha and with good corporate governance as moderation variables. Research in quantitative research terms. The population used is the primary consumer goods sector company listed on the Indonesia Stock Exchange for the period 2019-2022. The analysis method used is data panel regression and processing using Eviews software version 10. Research results show that profitability affects corporate value. However, growth opportunities and capital structures do not improve the value of the company. Good Corporate Governance is unable to accelerate profitability, growth opportunities and capital structure to corporate value.